PENGARUH KECERDASAN EMOSIONAL DAN BUDAYA ORGANISASI TERHADAP KINERJA KARYAWAN DENGAN KOMPETENSI KOMUNIKASI SEBAGAI VARIABEL MODERASI PADA DIVISI FOOD AND BEVERAGE DI HOTEL GRAN MELIA JAKARTA - Edvin Fairliantina (LPPM Universitas Asa Indonesia, 2019)
Purpose- The purpose of this study was to analyze the effect of emotional intelligence and organizational culture on employee performance with communication competence as a moderation variable in the Food and Beverage Divisionin Gran Melia Hotel, Jakarta. Design/methology/approach-The sample of this tudy was 73 employees at the Food and Beverage Division in Gran Melia Hotel, Jakarta. The sample technique usde is saturated sample due to limitation of staff’s number. Findings- The research result: 1) there is a significant direct effect of emotional intelligence variables on employee competency variables, (2) there is a significant direct effect organizational culture variables on communication competence variables, (3) there is a significant direct effect of emotional intelligence variables on employee performance variables, (4) there is direct significant organizational culture variables on employee performance variables, (5) there is a significant direct effect of communication competency variables on employee performance variables.